Impacto da intubação orotraqueal na deglutição do indivíduo pós-acidente vascular encefálico após cirurgia cardíaca - Almeida, Tatiana Magalhães De; Cola, Paula Cristina; Magnoni, Daniel; França, João Ítalo Dias; Germini, Michele Fca; Silva, Roberta Gonçalves Da (ABRAMO Associação Brasileira de Motricidade Orofacial, 2015)
PURPOSE: to associate the degree of oropharyngeal dysphagia and orotracheal intubation time in post stroke individuals after cardiac surgery.METHODS: a cross-sectional retrospective descriptive clinical study carried out by means of protocols data collection and chart records during six months in a public hospital of reference in cardiology. We analyzed 25 protocols and medical records of individuals undergoing cardiac surgery who evolved with stroke and were assisted by a team of speech and language pathology. The subjects were divided into two groups. Group I (GI) consisted of 10 individuals with orotracheal intubation less than 24 hours and Group II (GII) of 15 individuals with orotracheal intubation more than 24 hours. After performing swallowing clinical evaluation and analyzing the association between the clinical classification of degree of commitment for dysphagia and orotracheal intubation time.RESULTS: it was found that 40% of the individuals in GI presented mild dysphagia, 30% moderate and 20% severe. In GII, 13.3 % presented mild dysphagia, 33.3% moderate and 53.33% severe. There was a significant linear association between the degree of dysphagia and the duration of intubation (p = 0.031), indicating that the number of individuals with moderate and severe dysphagia was higher in the group with a longer intubation.CONCLUSIONS: we could observe that time of orotracheal intubation more than 24 hours increases the degree of oropharyngeal dysphagia in this population.

OBJETIVO:associar o grau de disfagia orofaríngea e o tempo de intubação orotraqueal no indivíduo pós-acidente vascular encefálico após cirurgia cardíaca.MÉTODOS:estudo clínico transversal descritivo, retrospectivo, realizado por meio da coleta de dados de protocolos e registros de prontuário, durante seis meses, em Hospital Público de Referência em Cardiologia. Foram analisados 25 protocolos e prontuários de indivíduos submetidos à cirurgia cardíaca, que evoluíram com acidente vascular encefálico e foram assistidos pela equipe de Fonoaudiologia. Os indivíduos foram divididos em dois grupos. O Grupo I (GI) constou de 10 indivíduos com intubação orotraqueal menor que 24 horas e o Grupo II (GII) de 15 indivíduos com intubação orotraqueal maior que 24 horas. Realizada avaliação clínica da deglutição e analisada a associação entre a classificação clínica do grau de comprometimento para disfagia e o tempo de intubação orotraqueal.RESULTADOS:verificou-se que no GI 40% apresentaram disfagia leve, 30% moderada e 20% grave. No GII 13,3% apresentaram disfagia leve, 33,3% moderada e 53,33% grave. Verificou-se associação linear significante entre o grau de disfagia e o tempo de IOT (p= 0,031), indicando que o número de indivíduos com disfagia moderada e grave foi maior no grupo com mais tempo de intubaçao.CONCLUSÕES:constatou-se que o tempo de intubação orotraqueal maior que 24 horas aumentou o grau da disfagia orofaríngea nesta população.
Impact of orotracheal intubation on a post stroke individual's swallowing after cardiac surgery
Keywords: swallowing disorders; stroke; cardiac surgery; Transtornos de Deglutição; Acidente Vascular Cerebral; Cirurgia Toracica